Pursuing God's will together : a discernment practice for leadership groups - Barton, R. Ruth, 1960- (Downers Grove, Ill. : IVP Books/Formatio, 2012)
In Pursuing God's Will Together, Transforming Center founder Ruth Haley Barton provides a trustworthy process that enables Christian leaders to actively seek God together. Based on her experience as well as consultations with pastors and other leaders, the step-by-step guidance, personal reflection questions and community practices will help your leadership team become a community for discernment.
The heart of spiritual leadership -- Learning to see -- Beginning with spiritual transformation -- Leaders who are discerning -- Community at the leadership level -- Values that undergird community -- Practices for opening to God together -- Practices for listening to each other -- A covenant that protects community -- Get ready: preparing for the discernment process -- Get set: from decision making to discernment -- Go!: discerning God's will together -- But does it work?
Title from PDF title page (viewed on Jan. 6, 2014).
Includes bibliographical references (pages [249]-253).
Keywords: Christian leadership; Church group work; Discernment (Christian theology); Decision making -- Religious aspects -- Christianity; RELIGION / Christian Ministry / Pastoral Resources; Electronic books